Heart insufficiency after combination of verapamil and metoprolol: A fatal case report and literature review - Eva A. Saedder; Asser Hedegård Thomsen; Jørgen Bo Hasselstrøm; Jakob Ross Jornil (Clinical Case Reports, 2019)
Abstract The combination of verapamil or diltiazem with beta‐blockers should be avoided because of potentially profound adverse effects on AV (atrioventricular) nodal conduction, heart rate, or cardiac contractility. This effect is unpredictable but may be enhanced due to CYP2D6 poor metabolizer status which could be a special vulnerability factor.